FAIRYTALE MOTIVE OF BERLIN TEXT IN NOVEL “SEVENTEEN MOMENTS OF SPRING” BY Yu. SEMENOV - Daryna O. Holub (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
Urban text is a phenomenon that has been studied in both domestic and foreign literary studies. Representatives of the Tartu-Moscow semiotic school Yu.M. Lotman, B.M. Gasparov, V.N. Toporov, etc. are at the origin of the study of the image of the city and urban texts in literary studies, which began only in the 1970s. Intensive study of the specifics of the text in literary theory was developed in the structuralist concepts of R. Bart, Ts. Todorov and Yu. Kristeva. However, despite the large number of scholarly works on the topic of urban text, texts from a different perspective, namely the texts of a military city in the 30s and 40s having its difficult time when cultural monuments were erased from the face of the earth and old traditions remained to live among ruins and maimed destinies, remained unexamined. This is why the article looks at the urban text, namely the Berlin text, the picture of which is painted by Yu. Semenov in his novel “Seventeen Moments of Spring”, telling about the activities of the Soviet intelligence officer Isayev-Stierlitz in Nazi Germany in 1945. The aim is therefore to study the Berlin text in a novel through the prism of fairytale poetics, applying historical and literary, cultural and historical, and typological research methods. Berlin, against the background of which the events in Semenov’s novel unfold, is presented in a very concise way, without any emphasis on architectural monuments or historical sites of the city, without anything that the citizens of Berlin liked and that has lost its value since its rapid militarisation. On the contrary, none of the characters in Semenov’s novel have any particular attachment to the city, it has already been lost, as each of them understands its doom resulting from the end of the war. At the same time, it is in this city where the Soviet intelligence officer will have a difficult task: to do everything possible to reach those at the top of Nazi Germany who are planning separate negotiations with the allies and to disrupt them. His activities on the verge of human ability are viewed through the prism of a fairy tale (by V. Propp), where Isaev-Stierlitz acts as a fairytale character operating in Berlin, on its outskirts and outside the country. A safe house in a forbidden forest on the outskirts of the city, crossing the border into Switzerland through a “transfer corridor”, the moment when he returns in the role of a “knowing know-nothing” that gives a note of incompleteness to the novel, are the parts of the fairytale motive of the Berlin text. If the moment of the crossing the border is the axis of a magical fairy tale, then in the Berlin text of Yu. Semenov’s novel “Seventeen Moments of Spring” the doom of the city and its imminent death is nothing more than the embodiment of a “vertical text” (by A. Eremenko) that is woven into the novel and forms its fairytale meaning. As the novel’s finale approaches, the Berlin text loses its meaning. The war is so powerful that the taste of victory after the completed task is being replaced by a sense of devastation for both Stierlitz and the huge capital, which has promised to be no more, no less, the capital of the world, now partially in ruins, surviving its last days